Progression of keratoconus in the contralateral eye following acute corneal hydrops: A retrospective study - James Steven Lewis; Charles N.J. McGhee; Jay Meyer (PLoS ONE, 2025)
Keratoconus is a progressive eye disease characterised by thinning and bulging of the cornea, leading to distorted vision. Acute corneal hydrops, a rare and severe complication of keratoconus, occurs when fluid accumulates in the cornea due to a sudden break in its innermost layer, often causing pain, significant visual impairment, and sometimes requiring corneal transplantation. To better understand the risk of disease progression in the contralateral (unaffected) eye, we conducted a retrospective study at two major tertiary hospitals in Auckland, New Zealand. The study included 45 eyes from 45 patients presenting with acute corneal hydrops. Inclusion and exclusion criteria were rigorously applied to ensure that only patients eligible for corneal collagen crosslinking (CXL) at baseline were included, enhancing the clinical relevance of the findings. Patients were followed for a mean duration of 4.73 years. The results showed that 67% of contralateral eyes exhibited progression in at least one tomographic parameter, with 53.3% demonstrating progression in both anterior curvature and corneal thickness parameters. Higher baseline anterior curvature values and male sex were significantly associated with an increased risk of progression (p = 0.022 and p = 0.046, respectively). Nearly half of the eyes with progression had a thinnest corneal thickness of ≥400μm, making them eligible for CXL at initial presentation. However, 36% of these eligible eyes dropped below this threshold over the follow-up period, underscoring the importance of timely intervention to preserve treatment options. These findings highlight the importance of regular monitoring of the contralateral eye following acute corneal hydrops, particularly in male patients or those with advanced baseline disease. Immediate CXL may be considered in select cases to prevent disease progression. This study also emphasises the need for early intervention strategies and targeted healthcare services for populations at higher risk, including Māori and Pacific Peoples in Aotearoa-New Zealand, who experience disproportionately high burdens of keratoconus and health inequities.